Endothelial NOX5 Expression Modulates Thermogenesis and Lipolysis in Mice Fed with a High-Fat Diet and 3T3-L1 Adipocytes through an Interleukin-6 Dependent Mechanism - Jorge G. García; Carlos de Miguel; Fermín I. Milagro; Guillermo Zalba; Eduardo Ansorena (MDPI AG, 2021)
Obesity is a global health issue associated with the development of metabolic syndrome, which correlates with insulin resistance, altered lipid homeostasis, and other pathologies. One of the mechanisms involved in the development of these pathologies is the increased production of reactive oxygen species (ROS). One of the main producers of ROS is the family of nicotinamide adenine dinucleotide phosphate (NADPH) oxidases, among which NOX5 is the most recently discovered member. The aim of the present work is to describe the effect of endothelial NOX5 expression on neighboring adipose tissue in obesity conditions by using two systems. An in vivo model based on NOX5 conditional knock-in mice fed with a high-fat diet and an in vitro model developed with 3T3-L1 adipocytes cultured with conditioned media of endothelial NOX5-expressing bEnd.3 cells, previously treated with glucose and palmitic acid. Endothelial NOX5 expression promoted the expression and activation of specific markers of thermogenesis and lipolysis in the mesenteric and epididymal fat of those mice fed with a high-fat diet. Additionally, the activation of these processes was derived from an increase in IL-6 production as a result of NOX5 activity. Accordingly, 3T3-L1 adipocytes treated with conditioned media of endothelial NOX5-expressing cells, presented higher expression of thermogenic and lipolytic genes. Moreover, endothelial NOX5-expressing bEnd.3 cells previously treated with glucose and palmitic acid also showed interleukin (IL-6) production. Finally, it seems that the increase in IL-6 stimulated the activation of markers of thermogenesis and lipolysis through phosphorylation of STAT3 and AMPK, respectively. In conclusion, in response to obesogenic conditions, endothelial NOX5 activity could promote thermogenesis and lipolysis in the adipose tissue by regulating IL-6 production.